The impact of serotype-specific vaccination on phylodynamic parameters of Streptococcus pneumoniae and the pneumococcal pan-genome. - Taj Azarian; Lindsay R Grant; Brian J Arnold; Laura L Hammitt; Raymond Reid; Mathuram Santosham; Robert Weatherholtz; Novalene Goklish; Claudette M Thompson; Stephen D Bentley; Katherine L O'Brien; William P Hanage; et al. (PLoS Pathogens, 2018)
In the United States, the introduction of the heptavalent pneumococcal conjugate vaccine (PCV) largely eliminated vaccine serotypes (VT); non-vaccine serotypes (NVT) subsequently increased in carriage and disease. Vaccination also disrupts the composition of the pneumococcal pangenome, which includes mobile genetic elements and polymorphic non-capsular antigens important for virulence, transmission, and pneumococcal ecology. Antigenic proteins are of interest for future vaccines; yet, little is known about how the they are affected by PCV use. To investigate the evolutionary impact of vaccination, we assessed recombination, evolution, and pathogen demographic history of 937 pneumococci collected from 1998-2012 among Navajo and White Mountain Apache Native American communities. We analyzed changes in the pneumococcal pangenome, focusing on metabolic loci and 19 polymorphic protein antigens. We found the impact of PCV on the pneumococcal population could be observed in reduced diversity, a smaller pangenome, and changing frequencies of accessory clusters of orthologous groups (COGs). Post-PCV7, diversity rebounded through clonal expansion of NVT lineages and inferred in-migration of two previously unobserved lineages. Accessory COGs frequencies trended toward pre-PCV7 values with increasing time since vaccine introduction. Contemporary frequencies of protein antigen variants are better predicted by pre-PCV7 values (1998-2000) than the preceding period (2006-2008), suggesting balancing selection may have acted in maintaining variant frequencies in this population. Overall, we present the largest genomic analysis of pneumococcal carriage in the United States to date, which includes a snapshot of a true vaccine-naïve community prior to the introduction of PCV7. These data improve our understanding of pneumococcal evolution and emphasize the need to consider pangenome composition when inferring the impact of vaccination and developing future protein-based pneumococcal vaccines.